Giant kelp, Macrocystis pyrifera, increases faunal diversity through physical engineering - Miller, Robert J.; Lafferty, Kevin D.; Lamy, Thomas; Kui, Li; Rassweiler, Andrew; Reed, Daniel C. (Proceedings of the Royal Society. B, Biological sciences, 2018)
Foundation species define the ecosystems they live in, but ecologists have often characterized dominant plants as foundational without supporting evidence. Giant kelp has long been considered a marine foundation species due to its complex structure and high productivity; however, there is little quantitative evidence to evaluate this. Here, we apply structural equation modelling to a 15-year time series of reef community data to evaluate how giant kelp affects the reef community. Although species richness was positively associated with giant kelp biomass, most direct paths did not involve giant kelp. Instead, the foundational qualities of giant kelp were driven mostly by indirect effects attributed to its dominant physical structure and associated engineering influence on the ecosystem, rather than by its use as food by invertebrates and fishes. Giant kelp structure has indirect effects because it shades out understorey algae that compete with sessile invertebrates. When released from competition, sessile species in turn increase the diversity of mobile predators. Sea urchin grazing effects could have been misinterpreted as kelp effects, because sea urchins can overgraze giant kelp, understorey algae and sessile invertebrates alike. Our results confirm the high diversity and biomass associated with kelp forests, but highlight how species interactions and habitat attributes can be misconstrued as direct consequences of a foundation species like giant kelp.